Allelopathic activity of Eragrostis plana Nees on the germination of persian clover, rice and white oats - Quatrin, Marciéli; Mendes, Yago Luís Nóbrega; Brasil, Nicolas Gibran Marques; Bevilaqua, Daiane Balconi; Stefanello, Raquel; Vestena, Silvane (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Eragrostis plana Nees is an exotic Poaceae with invasive potential in natural grassland areas of southern South America, due to its biological and ecological characteristics. This study was carried out to evaluate the possible allelopathic effect of E. plana on the germination of Trifolium resupinatum (persian clover), Oryza sativa (rice) and Avena sativa (white oats) seeds. To obtain the aqueous extract, previously dried aerial parts (leaf and stem) were used at a concentration of 1 g 10 mL-1. Four different concentrations were used (25, 50, 75, and 100%) and the control (distilled water), with four replicates for each treatment. At the end of the experiment, the following parameters were assessed: first count, germination percentage, initial length, and dry mass of the seedlings. It was found that the aqueous extracts of E. plana significantly reduced all the parameters evaluated in the three agricultural species. For rice, the 100% concentration was the most inhibitory; for oats, there was a reduction in the parameters assessed from 75% onwards, except for biomass, which was reduced at the 100% concentration. Finally, persian clover showed a significant reduction in all the variables analyzed at the highest concentration. The results indicate that the aqueous extracts of E. plana have a negative influence on the germination and development of rice, oat, and persian clover seedlings; therefore, care should be taken when intercropping these cultivated species with this species, which is considered to be allelopathic.